Cyber Adventure - An Education 2D RPG Game to teach Cybersecurity Concepts - Deshmukh, Siddharth (Wellington Faculty of Engineering Symposium, 2023)
In today’s digital age, there exists a pressing need to educate students about cybersecurity principles. However, traditional teaching methods can often be inaccessible or tedious. Recognizing this gap, this project, proposes a novel approach to addressing this educational challenge. It introduces a 2D RPG web-based game which is designed to create an engaging learning environment for students. Beyond just mere entertainment, this game integrates interactive mini-games and puzzles tailored to convey core cybersecurity concepts. These puzzles are carefully crafted to provide players with hands-on experience to face real-world scenarios and challenges in a fun, virtual environment. The aim of the project is not just to educate but to captivate beginners, especially those with minimal prior knowledge in cybersecurity. By transforming passive learning into an active discovery process, this approach has the ability to ignite a passion for cybersecurity in students. Initial user feedback and surveys suggest a promising trend: participants consistently report heightened interest and retention of the subject matter. In conclusion, the project offers a novel solution to a contemporary educational challenge, presenting an instructive tool that makes learning cybersecurity both enjoyable and effective, paving the way for innovative teaching methods in the digital era.